2001
DOI: 10.1053/jlts.2001.22180
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a liver allocation plan using a continuous medical severity score that de-emphasizes waiting time

Abstract: Liver allocation remains problematic because current policy prioritizes status 2B or 3 patients by waiting time rather than medical urgency. On February 21, 2000, we implemented a variance to the United Network for Organ Sharing liver allocation policy that redefined status 2A by much more rigid, definable criteria and prioritized status 2B patients by using a continuous medical urgency score based on the Child-Turcotte-Pugh score and other medical conditions. In this system, waiting time is used only to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 5 publications
4
37
0
2
Order By: Relevance
“…Use of a continuous score has been shown to decrease mortality in patients waiting for OLT. 8 However, it is not clear if the improvement of pretransplant survival comes at risk of reducing posttransplant survival. Preliminary studies have shown that in the short term, MELD does not impact patient survival after OLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of a continuous score has been shown to decrease mortality in patients waiting for OLT. 8 However, it is not clear if the improvement of pretransplant survival comes at risk of reducing posttransplant survival. Preliminary studies have shown that in the short term, MELD does not impact patient survival after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…The application of a continuous scale that de-emphasizes waiting time for status 2B candidates resulted in a significant reduction of overall deaths on the wait list. 8 The Model for End-Stage Liver Disease (MELD) is a similar continuous scale that has been adopted by the United Network for Organ Sharing (UNOS) to stratify patients on the liver transplant wait list. 1 The MELD scale originally was designed to assess short-term prognosis in patients with hepatic cirrhosis who underwent transjugular intrahepatic portosystemic shunt (TIPS).…”
mentioning
confidence: 99%
“…Reduced-size liver transplantation7 was the wellspring for this effort followed by cadaveric split liver transplantation,*-1° adult-to-pediatric living related, and more recently adult living donor liver transplantation (ALDLT). "-'* In Europe and the United States, right hepatic lobes (segments [5][6][7][8] are by far the most common grafts u~ed,l5-~* because they represent the logical balance of providing the recipient with sufficient liver mass to overcome the small-for-size syndrome that is observed following left lobe graftingl5 without compromising donor ~afety.~5 However, it is exceedingly difficult to accurately determine recipient outcomes in the Untied States, because only a few centers have published comprehensive reports. l5-l9 Furthermore, fewer reports have provided comparisons to whole organ …”
mentioning
confidence: 99%
“…We must wait and see if MELD, prospectively applied to the transplant waiting list, will give the better outcomes we seek. A modification of the CTP and UNOS status system that de-emphasizes waiting time 13 improves both donor organ utilization and patient survival, as recently reported. Will "Child," recently come of age have to retire soon or can we meld the 40 years of experience of CTP with the emerging new index of severity of liver disease and allow Child a few more years of productive existence?…”
mentioning
confidence: 67%